2016
DOI: 10.1590/s1677-5538.ibju.2016.0211
|View full text |Cite
|
Sign up to set email alerts
|

Outcome analysis of holmium laser and pneumatic lithotripsy in the endoscopic management of lower ureteric calculus in pediatric patients: a prospective study

Abstract: Objective:To analyse outcomes of holmium laser and pneumatic lithotripsy in treatment of lower ureteric calculus in pediatric patients.Materials and methods:Prospective study conducted between August 2013 and July 2015. Inclusion criteria were lower ureteric calculus with stone size ≤1.5cms. Exclusion criteria were other than lower ureteric calculus, stone size ≥1.5cms, congenital renal anomalies, previous ureteral stone surgery. Patients were divided into two groups. Group A underwent pneumatic and group B un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…10 Jhanwar et al conducted another study by analyzing the outcomes of Ho: YAG LL and PL in children and concluded that both techniques were equally efficacious; however, holmium laser required more expertise and was a costly alternative and comparatively more advantageous in impacted calculus. 11 Maghsoudi et al showed that Ho: YAG laser had more advantages over PL due to a higher efficacy of stonefree rate and a lower rate of upward displacement of ureteral stones, while their complications were the same and very rare. 12 Razzaghi et al conducted a review of the literature on laser application in Iran and revealed that this technology has not yet found its position in Iran, especially in the field of urology, it might be due to problems in accessibility of laser devices and inadequacy of knowledge about this technology.…”
Section: Discussionmentioning
confidence: 99%
“…10 Jhanwar et al conducted another study by analyzing the outcomes of Ho: YAG LL and PL in children and concluded that both techniques were equally efficacious; however, holmium laser required more expertise and was a costly alternative and comparatively more advantageous in impacted calculus. 11 Maghsoudi et al showed that Ho: YAG laser had more advantages over PL due to a higher efficacy of stonefree rate and a lower rate of upward displacement of ureteral stones, while their complications were the same and very rare. 12 Razzaghi et al conducted a review of the literature on laser application in Iran and revealed that this technology has not yet found its position in Iran, especially in the field of urology, it might be due to problems in accessibility of laser devices and inadequacy of knowledge about this technology.…”
Section: Discussionmentioning
confidence: 99%
“…Together with inaccurate operations, the fragile polyps in such injured tissues or mucous membranes can cause bleeding. Unclear vision can also lead to surgical failure [23]. An intraoperative ureteral mucosal injury can easily lead to postoperative ureteral stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Jhanwar et al in 2016 the authors also reported that the stone free rate for lower ureteric calculi was similar with Pneumatic Vs Laser lithotripter (100% Vs 94.73%). 18 Similar efficacy has been advocated in many literatures for Laser lithotripter. 19 Another study reported 100% immediate SFR in LL group (N=12) and 42.9% in PL group (N=14) p=0.001.…”
Section: European Association Of Urology (Eau) Recommendsmentioning
confidence: 60%